2003
DOI: 10.1021/ja0376893
|View full text |Cite
|
Sign up to set email alerts
|

Optical Rotation of Noncovalent Aggregates

Abstract: Dilute solutions of (R)-(-)-pantolactone in CCl4 were studied by polarimetry in conjunction with theoretical calculations of [alpha]D. Our data demonstrate that the self-association of a chiral solute results in a change in [alpha]D that can be accounted for by the presence of hydrogen-bonded dimeric species. The theoretical analysis predicts a concentration-dependent specific rotation in good agreement with experiment. Further exploration of monomer and dimer [alpha]D differences, through atomic map analysis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
54
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 25 publications
3
54
0
Order By: Relevance
“…Both scale as the same inverse power of electron-nucleus distance, i.e., ͉r i − R I ͉ −2 , but K n I also depends on R I . The present findings confirm those of the previous paper on H 2 butions are virtually the same, and ͓F , K͑O 1 ͔͒ ones are slightly different on the scale of the plot, defining atomic contributions in the torque scheme. ͓F͑O 1 ͒ , L͔ and ͓F͑O 1 ͒ , K͔ curves are close to one another, but they are characterized by a different pattern with a minimum at conformations in the proximity of ⌽ = −30°.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Both scale as the same inverse power of electron-nucleus distance, i.e., ͉r i − R I ͉ −2 , but K n I also depends on R I . The present findings confirm those of the previous paper on H 2 butions are virtually the same, and ͓F , K͑O 1 ͔͒ ones are slightly different on the scale of the plot, defining atomic contributions in the torque scheme. ͓F͑O 1 ͒ , L͔ and ͓F͑O 1 ͒ , K͔ curves are close to one another, but they are characterized by a different pattern with a minimum at conformations in the proximity of ⌽ = −30°.…”
Section: Resultssupporting
confidence: 92%
“…Since its discovery in the beginning of the 19th century it has been used as an experimental tool to measure the enantio purity of chemical compounds. 1 Among the different properties that influence the optical rotatory power ͑ORP͒, several articles have been devoted recently to the effect of the molecular aggregation of the molecule of interest with itself [2][3][4] or with the solvent. [5][6][7] The idea that molecular properties can be rationalized in terms of atomic contributions, transferable from molecule to molecule, constitutes an object of interest from the early days of chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…Goldsmith et al studied the influence of the dimer formation on the OR of pantolactone. 41 The results were compared with experimental OR as a function of the pantolactone/CCl 4 concentration. The authors found a strong effect of aggregation on OR.…”
Section: Introductionmentioning
confidence: 99%
“…A racemic mixture containing equal amounts of right-handed and left-handed forms shows no optical activity. Such structure-property relationship makes optical rotation suitable for versatile applications, ranging from chiral analysis in chemistry, pharmaceutical and biological industries to electro-optical elements12.…”
mentioning
confidence: 99%